PRODUCTIVE IMPACT OF FORAGE GRASSES AND LEGUMES IN THE CENTRAL JUNGLE OF PERU (Nativa, 2024)
The study's objective was to evaluate the establishment and production of forage grasses and legumes in acidic and degraded soils of Puerto Bermúdez, Peru. Two treatments were experimented with, consisting of 3 grasses (Brachiaria decumbens, Andropogon gayanus and Brachiaria dictyoneura) and 12 legumes (Stylosanthes guianensis, Desmodium ovalifolium, Centrosema pubescens, Zornia latifolia, Stylosanthes capitata, Centrosema macrocarpum, Centrosema sp., Centrosema brasiliensis, Centrosema arenarium, Zornia glabra, Aeschynomene histrix, and, Pueraria phaseoloides), in monoculture plots, using a Completely Randomized Design, showing statistically significant differences. The grass that had the highest plant height (73 ± 0.01 cm) was Andropogon gayanus, dry matter (4,325 ± 435.88 kg ha-1), and the percentage of cover (100% m-2) was Brachiaria dictyoneura. The legume that stood out in plant height was Stylosanthes capitata (34 ± 0.01 cm), in dry matter, Stylosanthes guianens (2265 ± 294.95 kg ha-1), and, in percentage of cover (100%), Stylosanthes guianens stood out, Desmodium ovalifolium, Zornia latifolium, Pueraria phaseoloides, respectively. The study's findings highlight the significant differences in the performance of certain grasses and legumes in acidic and degraded soils and the need for further research on associated crops, fertilization, and agronomic management to fully exploit their potential.Keywords: pasture establishment; forage height; dry mass production; coverage percentage; tolerance to soil acidity. Impacto produtivo das gramíneas e leguminosas forrageiras na Selva Central do Peru RESUMO: O objetivo do estudo foi avaliar o estabelecimento e produção de gramíneas e leguminosas forrageiras em solos ácidos e degradados de Puerto Bermúdez, Peru. Foram experimentados dois tratamentos, compostos por 3 gramíneas (Brachiaria decumbens, Andropogon gayanus e Brachiaria dictyoneura) e 12 leguminosas (Stylosanthes guianensis, Desmodium ovalifolium, Centrosema pubescens, Zornia latifolia, Stylosanthes capitata, Centrosema macrocarpum, Centrosema sp., Centrosema brasiliensis, Centrosema arenarium, Zornia glabra, Aeschynomene histrix e Pueraria phaseoloides), em parcelas de monocultivo, utilizando delineamento inteiramente casualizado, apresentando diferenças estatisticamente significativas. A gramínea que apresentou maior altura de planta (73±0,01 cm) foi Andropogon gayanus, massa seca (4.325±435,88 kg ha-1) e porcentagem de cobertura (100% m-2), foi Brachiaria dictyoneura. A leguminosa que se destacou em altura de planta foi Stylosanthes capitata (34±0,01cm), em massa seca Stylosanthes guianens (2265±294,95 kg ha-1) e, em porcentagem de cobertura (100%), Stylosanthes guianens se destacou, Desmodium ovalifolium, Zornia latifolium, Pueraria phaseoloides, respectivamente. Concluindo que o melhor desempenho é atribuído a uma maior adaptação das gramíneas às condições edáficas limitantes e à sua eficiência fotossintética, enquanto as leguminosas apresentaram menor tolerância à acidez do solo devido ao efeito do alumínio (Al). Mais pesquisas são necessárias, como culturas associadas, fertilização e manejo agronômico.Palavras-chave: estabelecimento de pastagem; altura de forragem; produção de massa seca; porcentagem de cobertura; tolerância à acidez do solo.